2008
DOI: 10.1016/j.jep.2008.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Toona sinensis Roem tender leaf extract inhibits SARS coronavirus replication

Abstract: This paper reports for the first time that extract from a vegetable, the tender leaf of Toona sinensis Roem, can inhibit SARS-CoV in vitro. Thererfore, the tender leaf of Toona sinensis Roem may be an important resource agninst SARS-CoV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(95 citation statements)
references
References 12 publications
1
92
0
2
Order By: Relevance
“…Flavonoids, [26][27][28] limonoids, 10,17,29 and triterpenoids have been identified from the leaves and stems of this plant. The reported biological activities of C. sinensis include antioxidant activity, 19,30 antitumor effects, [11][12][13]24 inhibition of virus replication, 14 and hypoglycemic effects. 15 However, there has been little research on the activation or regulation of expression of antioxidant enzymes by C. sinensis.…”
Section: Sod Reacts With Omentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids, [26][27][28] limonoids, 10,17,29 and triterpenoids have been identified from the leaves and stems of this plant. The reported biological activities of C. sinensis include antioxidant activity, 19,30 antitumor effects, [11][12][13]24 inhibition of virus replication, 14 and hypoglycemic effects. 15 However, there has been little research on the activation or regulation of expression of antioxidant enzymes by C. sinensis.…”
Section: Sod Reacts With Omentioning
confidence: 99%
“…[11][12][13] Recent studies have also demonstrated the hypoglycemic and antiviral effects of the extract of C. sinensis leaves. 14,15 Recently, our group reported that the dichloromethane (DCM)-soluble fraction from C. sinensis significantly inhibits lipopolysaccharide-induced nitric oxide and ROS production as well as the expressions of inducible nitric oxide synthase and cyclooxygenase 2 via an MAPK pathway. 16 Other studies have identified various phytochemicals from this plant, including flavonoids, limonoids and terpenoids.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, almost all parts of T. sinensis including seed, bark, root bark, petioles, and leaves have a number of traditional Chinese medicinal values (for example: used as febrifuge, astringent, carminative, and used for enteritis and dysentery treatments) (Xien, 1996;Edmonds and Staniforth, 1998). More recently, various other biological values discovered from the T. sinensis leaf extracts have been reported: anti-cancer (Chang et al, 2002;Wang et al, 2010;Yang et al, 2010), antiinflammatory (Yang et al, 2006), anti-diabetes (Hsu et al, 2003), anti-neoplastic effect (Chia et al, 2010), and inhibitory effects on Leydig cell steroidogenesis (Poon et al, 2005), severe acute respiratory syndromes and coronavirus replication (Chen et al, 2008), and antitumor (Yang et al, 2013). In addition, T. sinensis trunk is a good source of hardwood (Edmonds and Staniforth, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the plant possesses many biological functions such as antitumor activity [2], antioxidant capacity [3], and anti-inflammatory properties [4]. It is also used for treating severe acute respiratory syndrome [5], and for improving hyperglycemia and dyslipidemia [6]. The young leaves of TS are popular in traditional Chinese medicines and have been used for long as a safe vegetable source [7].…”
Section: Introductionmentioning
confidence: 99%